Google Colaboratory : Tool for Deep Learning and Machine Learning Applications - J., Praveen Gujjar; V., Naveen Kumar (Indian Journal of Computer Science, 2021)
Google Colaboratory is a cloud based service which is also known as Colab. Google Colab is based on Jupyter Notebook where machine learning and deep learning concepts can be implemented. Google Colab provides free access to Graphical Processing Unit (GPU) which is very much required to disseminate deep learning concepts. This paper presents a tool for performing a deep learning application which is in Google Colaboratory and also discusses the performance of transfer learning model xlm and MobileNetV2 in Google colab. This GPU may help many researchers to carry out their research work with high end infrastructure to implement the concept of machine learning and deep learning concept.